The large avalanches of the Northern Neuquén region between 36°-38°S: A proposed seismic induction - González Díaz, E.F. (2006)
Studies performed during the last five years have shown the existence of 74 prehistoric rock-avalanches in the northern Neuquén Andes (36°-38°S). These are mainly related to volcanic grounds of Pliocene to Pleistocene age corresponding to the Hualcupén Formation. In this work we describe their main characteristics and general homogeneous morphology. They are also characterized by a single tectonic control associated with the occurrence of their break-away and mainly postglacial ages, fact revealed by their systematic position into previous glacial valleys and limited radiometric ages. The obstruction produced by these features altered the shape of the valleys giving to local lakes. Eighteen percent of the cases are characterized by landslide dams preserved nowadays while only six percent by ephemeral ones. Two of the dams were actually catastrophically collapsed: the Cerro Pelán and Navarrete rock-avalanches: The former in Barrancas river valley with the consequent formation of the Carrilauquen lake and the later with the generation of Navarrete lake. The Carrilauquen's dam broke during historical times (29/12/1914) forming an outburst-flood that passed from the Barrancas valley to the Colorado river valley destroying their local economy and reaching after 1,500 km the Atlantic coast. The highest computed volumes in the entire region for the deposits related to rock-avalanches correspond to Varva Co Campos avalanche (3 km3). Cosmogenic isotopes have revealed its age and the age of the neighbor deposit of Varvar Co Tapia rock-avalanche, resulting in 30 ka and 60 ka respectively. Further cosmogenic isotope data revealed that the Cerro PeMn avalanche is only 2 ka. A wrong assumption, presently revaluated, was related to the assignment of these deposits to glacial accumulations because of their chaotic structure, their hummocky topography and the induced dams. Finally, several topographic, geomorphological and seismotectonic criteria are exposed to prove a seismic trigger for these avalanches. Graphics and one table are used to display the distribution of their deposits and its dose association with the orogenic front at these latitudes and the crustal seismicity of the region. © 2006 Asociación Geológica Argentina.